Characterization of immune response to novel HLA-A2-restricted epitopes from zinc transporter 8 in type 1 diabetes. Issue 6 (3rd February 2016) - Xu, Xinyu; Gu, Yong; Bian, Lingling; Shi, Yun; Cai, Yun; Chen, Yang; Chen, Heng; Qian, Li; Wu, Xiangmei; Xu, Kuanfeng; Mallone, Roberto; Davidson, Howard W.; et al.
Abstract: Objective: ZnT8-specific CD8+ T cells in human type 1 diabetes (T1D) have been reported recently, although the results from different laboratories are inconsistent. We aimed to characterize these ZnT8 specific CD8+ T cells and validate assays to screen peptide libraries. Methods: We screened HLA-A2-restricted T cell candidate peptides of ZnT8 with different methods including computer algorithms, MHC-peptide binding and dissociation assays in T2 cell line, identification in HLA-A2 transgenic (Tg) mice and in vivo CTL assays. Then ELISpot assay was used to measure peptide-reactive T cell responses in 49 HLA-A2-restricted T1D patients. Results: We demonstrated that ZnT8107–116(115), ZnT8110–118, and ZnT8177–186 were novel HLA-A*0201-restricted CTL epitopes in T1D patients. ZnT8107–116(115), ZnT8115–123, ZnT8153–161, ZnT8177–186 and ZnT8291–300 represent potentially major biomarkers for T1D. T cell responses against these epitopes showed different distributions between recently diagnosed and long-standing patients. Furthermore, they displayed discriminating performance among different ethnicities. We also compared the performance of the epitope identification strategies used herein. The epitopes which exhibited strong immunogenicity in HLA-A2 Tg mice were also well recognized by T1D patients. Conclusions: The differences in autoimmune T cell responses among T1D individuals may open new avenues toward T1D prediction and prevention. It also provides efficient strategies for immune intervention.